Does government support increase motivation of citizens to contribute to NGOs’ services: Yes or No? - Lucia Johanesová (Ekonomika a Spoločnosť)
Previous studies on the crowd-out effect in nonprofit organizations have primarily focused on more developed countries. However, transition processes in CEE countries caused changes in public administration creating opportunities for social capital development and outsourced provision of public services. Consequently, these countries, supported by EU programs, aim their strategies at the development of nonprofit organizations. In the CEE context, the term non-governmental organizations (NGOs’) is more appropriate, as it excludes government-owned organizations. The most active NGO sector in the regions of CEE is found among the Visegrad countries, with Slovakia having the highest number of NGOs per citizen in this group (70k). Such a large number of NGOs delivering various services requires support from multiple sources – private donations and various types of government support. The interaction between these funding sources depends on the marginal utility of the citizen using service provided by particular NGO. Based on citizen preferences, the amount of private donations depends on. The crowd-out effect explains the interaction between donations and public subsidies; therefore, the aims of this research paper is to analyse various type of government support and their effect on private donations in Slovak NGOs. Analysis has been performed by left-corner solution Tobit model. Results show that Slovak NGOs are mainly facing crowd-in effect due to low threshold of various supports. Crowd-out effect has been found in the education (regional and government level), sport (government level), membership and health organizations (regional level) and interest NGOs (local level).